Analisis Komunikasi Bisnis Online Shop Mantan Karyawan melalui Media Sosial Instagram - Eceh Trisna Ayuh; Hafri Yuliani (JOPPAS: Journal of Public Policy and Administration Silampari, 2021)
ABSTRACT The purpose of the study was to determine the online shop business communication of former employees through Instagram social media. The research method uses a qualitative descriptive method equipped with online media references. The results showed; 1. Products, products offered by online shops can be updated directly through the latest photos, live streaming, stories, and videos; 2. Price, publication through Instagram social media, allows all consumers to know firsthand the prices and discounts offered by online shops; 3. Place, Instagram allows every individual to open an online store without having to have a place of sale. 4. Promotion, promotions carried out by online shops are very easy, such as live streaming because they do not have to cost money, besides making videos and sharing them with all followers can be done directly. The conclusion of the study is that Instagram as a promotional media has been able to provide space to be able to promote all products. The conclusion of the study is that the communication of former employees in the online shop business has begun to develop so that it stimulates the community in the area to be able to compete not only in creating conventional stores but online stores. Keyword: Bisnis Communication, Place, Price, Product, Promotion